L’anthropomorphisme dans les contes pour enfants de Gabrielle Roy - Harvey, Carol (Cahiers franco-canadiens de l'Ouest)

(untitled) (Presses universitaires de Saint-Boniface (PUSB), 2022)
The four children’s stories in Gabrielle Roy’s collection Contes pour enfants («Ma vache Bossie», «Courte- Queue», «L’Espagnole et la Pékinoise» et «L’Empereur des bois») all focus on either domestic or wild animals. However, she often uses the literary technique of anthropomorphism, attributing human characteristics to the animals in her stories. This article aims to show the wide variety of narrative perspectives that Roy deploys by means of realistic or imaginary settings, human or animal protagonists, and interactions between humans and animals. Each story’s origin at a different point in Roy’s career is investigated, as well as its intentionality: was her children’s fiction simply entertainment or did she have didactic or ideological objectives?